2011
DOI: 10.2176/nmc.51.531
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategy for Intracranial Endodermal Cyst-Two Case Reports-

Abstract: Two cases of endodermal cyst of the posterior fossa are reported. A 12-year-old girl presented with severe headache and vomiting caused by increased intracranial pressure. Computed tomography and magnetic resonance (MR) imaging showed a cystic mass occupying the ambient and quadrigeminal cisterns. A 65-year-old woman presented with dizziness, and MR imaging revealed a cystic mass in the posterior fossa. The two patients underwent surgery for decompression and resection of the cyst. Surgical specimens of the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[12] A review of recurrent intracranial ECs showed that cyst walls were left in part in the initial surgery of most cases and recurrence occurs at the same site from 2 months to 32 years. [12,13] Recurrent ECs could proliferate, migrate, or become malignant, and some of them could release cystic contents into subarachnoid space leading to chemical meningoencephalitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] A review of recurrent intracranial ECs showed that cyst walls were left in part in the initial surgery of most cases and recurrence occurs at the same site from 2 months to 32 years. [12,13] Recurrent ECs could proliferate, migrate, or become malignant, and some of them could release cystic contents into subarachnoid space leading to chemical meningoencephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…[12] A review of recurrent intracranial ECs showed that cyst walls were left in part in the initial surgery of most cases and recurrence occurs at the same site from 2 months to 32 years. [12,13] Recurrent ECs could proliferate, migrate, or become malignant, and some of them could release cystic contents into subarachnoid space leading to chemical meningoencephalitis. [12,13] In 1 case of frontal lobe EC, Kitamura et al [7] reported that the cyst recurred at 34 months after cyst aspiration and there was occasional intense headache during the disease process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When this occurs, the cysts are frequently located in the posterior fossa. 3,4,6,7,10,12,13 The most common locations are anterior to the brainstem or within the fourth ventricle. The cysts have also been found in the cerebellopontine angle and clivus, but endodermal cysts in the petroclival area are extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are hypertintense on FLAIR images and may show mild restriction on diffusion-weighted images. 6,7,9,[11][12][13][14] In general, the absence of contrast enhancement of the cyst wall and of bone destruction is useful for distinguishing endodermal cysts from other cystic lesions such as cystic schwannoma and cystic meningiomas. 9,11,12 Therefore, a cystic tumor was included in the differential diagnosis because our case showed bone destruction and rim enhancement, which are rare in intracranial cysts.…”
Section: Discussionmentioning
confidence: 99%